Effects of Phoenix dactylifera Ajwa on Infection, Hospitalization, and Survival Among Pediatric Cancer Patients in a University Hospital: A Nonrandomized Controlled Trial. (January 2019) - Al Jaouni, Soad K.; Hussein, Abear; Alghamdi, Nora; Qari, Mohammed; El Hossary, Dalia; Almuhayawi, Mohammed S.; Olwi, Duaa; Al-Raddadi, Rajaa; Harakeh, Steve; Mousa, Shaker A.
This nonrandomized controlled trial determined the effects of Phoenix dactylifera palm date (Ajwa) intake on the number of infections and hospitalizations associated with fever, neutropenia, and mortality of pediatric cancer patients admitted between 2008 and 2017 to King Abdulaziz University Hospital (Jeddah, Saudi Arabia). Patients were eligible to be enrolled if they fulfilled the inclusion criteria, were not allergic to Ajwa, and were not enrolled in another study. Of 200 screened patients, 56 were included and 144 were excluded. Of the 56, 26 agreed to take Ajwa, and 30 served as controls. Both groups were assessed based on infection rates, frequency of hospital admissions for fever and neutropenia, and mortality rate. Background information regarding demographics, clinicopathological data, and treatment options was documented. Supplementation of Ajwa significantly reduced hospital admissions (for fever-associated neutropenia) and infections ( P = .009 and P < .001, respectively). Off-treatment did not significantly differ between the Ajwa and control groups. The Ajwa group had a better survival rate in comparison to the non-Ajwa group (stratified log-rank P = .005), where the main cause of death of patients in the non-Ajwa group was disease progression associated with infections (77%). In summary, Ajwa intake during the standard treatment of pediatric cancer patients improved their treatment outcome.